Chemotherapy-related leukopenia as a biomarker predicting survival outcomes in locally advanced cervical cancer. (January 2017) - Bogani, Giorgio; Sabatucci, Ilaria; Maltese, Giuseppa; Lecce, Francesca; Signorelli, Mauro; Martinelli, Fabio; Chiappa, Valentina; Indini, Alice; Leone Roberti Maggiore, Umberto; Borghi, Chiara; Fucà, Giovanni; Ditto, Antonino; et al.
Abstract: Objective: To investigate the impact of hematologic toxicity and leukopenia in locally advanced cervical cancer patients undergoing neoadjuvant chemotherapy (NACT). Study design: Data of consecutive patients undergoing platinum-based NACT followed by surgery were retrospectively searched in order to evaluate the impact of chemotherapy-related toxicity on survival outcomes. Toxicity was graded per the Common Terminology Criteria for Adverse Events (CTCAEv.4.03). Survival outcomes were evaluated using Kaplan-Meir and Cox hazard models. Results: Overall, 126 patients were included. Among those, 94 (74.6%) patients experienced grade2+ hematologic toxicity; while, grade2+ non-hematologic toxicity occurred in 11 (8.7%) patients. After a median follow-up of 37.1 (inter-quartile range, 12–57.5) months, 21 (16.6%) patients experienced recurrence. Via multivariate analysis, no factor was independently associated with disease-free survival; while a trend toward worse prognosis was observed for patients experiencing grade2+ leukopenia at cycle-3 (HR:3.13 (95%CI: 0.94, 10.3); p = 0.06). Similarly, grade2+ leukopenia (HR:9.98 (95%CI: 1.14, 86.6); p = 0.03), lymph-node positivity (HR:14.6 (95%CI:1.0, 214.4); p = 0.05) and vaginal involvement (HR:5.81 (95%CI:1.43, 23.6); p = 0.01) impacted on overall survival, at multivariate analysis. Magnitude of leukopenia correlated with survival (p<0.001). Conclusions: Although, our data have to be confirmed by prospective investigations, the present study shows an association between the occurrence of leukopenia and survival outcomes. NACT-related immunosuppression might reduce the response against the tumor, thus promoting cancer progression.